Increased marketing of MSME through quality product management, digital marketing and digital financing - Eka Patra; Hasrul; Herman; Hari Muharam; Lim Thien Sang; Rosle Mohidin (Journal of community engagement, 2024)
Caringin District is one of the sub-districts in Bogor Regency, West Java. The economy of the people of Caringin District depends on the agricultural, trade, industrial and manufacturing sectors. The majority of Micro, Small and Medium Enterprises (MSMEs) in Caringin District are in the trade and manufacturing sector, namely processed food and other similar snacks, clothing, craftsmen and convection entrepreneurs. The main challenges faced by MSME players are the lack of understanding and skills in using digital technology and the lack of the next generation to continue the business. The aim of this activity is to improve MSME marketing through quality product management, digital marketing and digital financing. The methods used are outreach to local government, training and observation. This activity involves MSME players, academics and government to help improve MSME marketing through quality product management, digital marketing and digital financing.